Environmental fluoxetine promotes skin cell proliferation and wound healing - Quentin Rodriguez-Barucg; Angel A. Garcia; Belen Garcia-Merino; Tomilayo Akinmola; Temisanren Okotie-Eboh; Thomas Francis; Eugenio Bringas; Inmaculada Ortiz; Mark A. Wade; Adam Dowle; Domino A. Joyce; Matthew J. Hardman; et al. (Environmental Pollution, 2024)

Morphological and physiological traits of Mediterranean sticklebacks living in the Camargue wetland ( Rhone river delta) - Khalid Rind; Quentin Rodriguez‐Barucg; Delphine Nicolas; Patricia Cucchi; Jehan‐Hervé Lignot (Journal of Fish Biology, 2020)
Three‐spined sticklebacks ( Gasterosteus aculeatus L.) living at the southern limit of the species distribution range could possess specific morphological and physiological traits that enable these fish to live at the threshold of their physiological capacities. Morphological analysis was carried out on samples of sticklebacks living in different saline habitats of the Camargue area (Rhone delta, northern Mediterranean coast) obtained from 1993 to 2017. Salinity acclimation capacities were also investigated using individuals from freshwater‐low salinity drainage canals and from mesohaline–euryhaline lagoons. Fish were maintained in laboratory conditions at salinity values close to those of their respective habitats: low salinity (LS, 5‰) or seawater (SW, 30‰). Fish obtained from a mesohaline brackish water lagoon (BW, 15‰) were acclimated to SW or LS. Oxygen consumption rates and branchial Na + /K + ‐ATPase (NKA) activity (indicator of fish osmoregulatory capacity) were measured in these LS or SW control fish and in individuals subjected to abrupt SW or LS transfers. At all the studied locations, only the low‐plated “leiurus” morphotype showed no spatial or temporal variations in their body morphology. Gill rakers were only longer and denser in fish sampled from the LS–freshwater (FW) drainage canals. All fish presented similar physiological capacities. Oxygen consumption rates were not influenced by salinity challenge except in SW fish transferred to LS immediately and 1 h after transfer. However, and as expected, gill NKA activity was salinity dependent. Sticklebacks of the Camargue area sampled from habitats with contrasted saline conditions are homogenously euryhaline, have low oxygen consumption rates and do not appear to experience significantly greater metabolic costs when challenged with salinity. However, an observed difference in gill raker length and density is most probably related to the nutritional condition of their habitat, indicating that individuals can rapidly acclimatize to different diets.